2017
DOI: 10.1016/j.cub.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of condensin and cohesin complexes driven by replacement of Kite by Hawk proteins

Abstract: SummaryMitotic chromosome condensation, sister chromatid cohesion, and higher order folding of interphase chromatin are mediated by condensin and cohesin, eukaryotic members of the SMC (structural maintenance of chromosomes)–kleisin protein family. Other members facilitate chromosome segregation in bacteria [1]. A hallmark of these complexes is the binding of the two ends of a kleisin subunit to the apices of V-shaped Smc dimers, creating a tripartite ring capable of entrapping DNA (Figure 1A). In addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 10 publications
2
108
0
Order By: Relevance
“…Whether cohesin binds as a single complex or 2 linked complexes and the mechanism by which cohesin associates with and then dissociates from DNA are also unknown . (d) SMC protein complexes in eukaryotes (cohesin, condensin, SMC5/6) and prokaryotes are tripartite ring‐shaped ATPases, composed of 2 SMC proteins, (light blue, dark blue), and a Kleisin linker protein (green) that joins their head domains and assembles the nucleotide binding domain, and to which one of a family of HEAT protein regulators (yellow) bind . Although they share a common architecture, these complexes vary in composition (SMCs are heterodimers in eukaryotes but homodimers in prokaryotes) and biological function, which may be influenced by the Kleisin subunit and/or the Kleisin‐associated HEAT‐family regulatory component…”
Section: Chromosome Loopsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether cohesin binds as a single complex or 2 linked complexes and the mechanism by which cohesin associates with and then dissociates from DNA are also unknown . (d) SMC protein complexes in eukaryotes (cohesin, condensin, SMC5/6) and prokaryotes are tripartite ring‐shaped ATPases, composed of 2 SMC proteins, (light blue, dark blue), and a Kleisin linker protein (green) that joins their head domains and assembles the nucleotide binding domain, and to which one of a family of HEAT protein regulators (yellow) bind . Although they share a common architecture, these complexes vary in composition (SMCs are heterodimers in eukaryotes but homodimers in prokaryotes) and biological function, which may be influenced by the Kleisin subunit and/or the Kleisin‐associated HEAT‐family regulatory component…”
Section: Chromosome Loopsmentioning
confidence: 99%
“…Cohesin was discovered and is best characterized in the budding yeast S. cerevisiae , for its role in holding sister chromatids together during mitosis until they are properly aligned and captured by the mitotic spindle and only then releasing them to allow for their segregation, Figure B. This function of cohesin may have evolved more recently than its role in loop formation …”
Section: Chromosome Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Scc1 interacts with the HEAT repeat Scc3 subunit which regulates chromatin association of cohesin. Using its flexible middle domain, Scc1 also serves as a docking platform for the HEAT repeat auxiliary proteins Pds5 and Scc2 [2629]. Scc2, with its stable binding partner Scc4, promotes cohesin loading [30] whereas Pds5, with its substoichiometric binding partner Wapl, dissociates cohesin from chromatin [3133].…”
Section: Topological Dna Binding By Cohesinmentioning
confidence: 99%
“…These results suggest that Wapl initially destabilizes the Smc3-Scc1 interaction and Pds5 then keeps the DNA transport gate open. Crystallographic and bioinformatic studies have shown that Pds5 and Scc2, as well as Scc3, are paralogs and share similar U-shaped structures that are composed of stacked HEAT repeat helices [2729,40]. Both Pds5 and Scc2 interact with the flexible middle domain of Scc1.…”
Section: Topological Dna Binding By Cohesinmentioning
confidence: 99%